2020
DOI: 10.1111/jan.14652
|View full text |Cite
|
Sign up to set email alerts
|

Practice nurses’ perceptions of their immunization role and strategies used to promote measles, mumps, and rubella vaccine uptake in 2014 – 2018: A qualitative study

Abstract: Aim: The aim of this study was to explore which aspects of their role practice nurses perceive to be most influential and the strategies they employ to promote the MMR vaccine. Design: Qualitative study employing in depth interviews. Method: Fifteen London based practice nurses, nine in 2014 and six in 2018, took part in semi-structured interviews that were audio recorded and transcribed verbatim. Qualitative content analysis was used to systematically manage, analyse, and identify themes. Results: Analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…To achieve high uptake of vaccines across all population groups in the UK, community engagement programmes built on established trusting relationships between health professionals, including nurses, and the voluntary sector, faith groups and community organisations are key (DHSC, 2021). Nurses also have a part to play in enabling appropriate information to be disseminated and promoted at the right time, at the right level and in the right format (Bajnok et al, 2018; Hill et al, 2021). Through the use of person‐centred approaches, building partnerships with individuals and communities, vaccine hesitancy may be addressed and vaccine confidence, rather than simply vaccine acceptance, may be achieved.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To achieve high uptake of vaccines across all population groups in the UK, community engagement programmes built on established trusting relationships between health professionals, including nurses, and the voluntary sector, faith groups and community organisations are key (DHSC, 2021). Nurses also have a part to play in enabling appropriate information to be disseminated and promoted at the right time, at the right level and in the right format (Bajnok et al, 2018; Hill et al, 2021). Through the use of person‐centred approaches, building partnerships with individuals and communities, vaccine hesitancy may be addressed and vaccine confidence, rather than simply vaccine acceptance, may be achieved.…”
Section: Discussionmentioning
confidence: 99%
“…In this frame of practice, establishing a trusting relationship and facilitating open and personalized discussions can positively influence immunization decisions. Exploring and responding to concerns and signposting to credible sources of information are also important (Hill et al, 2021). Core areas identified that should be addressed in discussions include the safety, efficacy and purpose of the vaccine (Larson et al, 2014).…”
Section: Empowering Individualsmentioning
confidence: 99%
See 2 more Smart Citations
“…There was also confusion about the particular role of health visitors in vaccination discussions (their primary role is in aiding parents with the care of new-born infants through domestic visits) as opposed to that of nurses or the child's GP. Similarly, Hill et al [51] interviewed 15 practice nurses about their role in promoting the MMR vaccine and what they perceived to be the most influential strategies in achieving this.…”
Section: Healthcare Worker Focus -4 Studiesmentioning
confidence: 99%